Perilaku Defensif Lebah Apis cerana Terhadap Stimulus Isopentil Asetat (IPA): Honey bee Apis cerana Defensive Behavior based on Isopentyl Acetate (IPA) Stimulus - Winnie, Ruth Martha; Raffiudin, Rika; Atmowidi, Tri (Departemen Biologi, Institut Pertanian Bogor, 2024)
Honey bee workers perform colony defense behavior to maintain colony integrity against predators. The aim of this research was to explore the response of A. cerana defensive behavior by using Isopentyl Acetate (IPA) as the stimulus which is the main volatile compound in the venom. Five concentrations of IPA volume i.e. 10, 20, 30, 40, and 50 µL IPA were used as the stimulus and each volume was pipetted to a cotton ball. The cotton ball was placed 10 cm in front of the hive entrance in oscillatory motion for five minutes. Natural defensive behavior of A. cerana (balling behavior), balling temperature and A. cerana predator were observed. Observation of defensive behavior was conducted by using colonies A. cerana obtained from Parung Panjang, Bogor and Nyalidung, Sukabumi; and using colonies A. cerana obtained from Sumedang and Banjarsari, Lebak. Based on the research, five A. cerana defensive behavior responses were observed, i.e.: guarding in front of bee hive entrance, recruitment at the hive entrance, fly toward the cotton ball, balling around the hive entrance, and balling on cotton ball. A. cerana showed defensive behavior due to IPA stimulus, however, there was no significant difference (P>0.05) with the variety IPA stimulus volume. We found the temperature of 44°C inside the natural balling of A. cerana defense behavior, as the colony defense mechanism in response to the natural predator Vespa sp. wasp.